2023
DOI: 10.1177/00220345231185288
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Mechanics of Chewing to Biology of the Junctional Epithelium

Abstract: The capacity of a tissue to continuously alter its phenotype lies at the heart of how an animal is able to quickly adapt to changes in environmental stimuli. Within tissues, differentiated cells are rigid and play a limited role in adapting to new environments; however, differentiated cells are replenished by stem cells that are defined by their phenotypic plasticity. Here we demonstrate that a Wnt-responsive stem cell niche in the junctional epithelium is responsible for the capability of this tissue to quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Using a variety of injury repair models, we demonstrated that oral epithelial repair is generally made possible by tissue-resident stem cell niches (Byrd et al, 2019;Yuan et al, 2019;Yuan, Chen, Gauer, et al, 2020;. Under homeostatic conditions, these epithelial niches produce daughter cells that contribute to the continuous turnover of the epithelia (Byrd et al, 2019;Tanaka et al, 2021;Yuan et al, 2019Yuan et al, , 2023Yuan, Chen, Gauer, et al, 2020;. In response to injury, for example, extraction of a tooth, gingivectomy and placement of an implant, these same epithelial niches dramatically increase production of mitotically active daughter cells, which then migrate widely to occupy and heal the damaged areas (Yuan et al, 2021;Yuan, Chen, Gauer, et al, 2020;.…”
Section: A Model To Explain the Rate Of Pie Maturationmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a variety of injury repair models, we demonstrated that oral epithelial repair is generally made possible by tissue-resident stem cell niches (Byrd et al, 2019;Yuan et al, 2019;Yuan, Chen, Gauer, et al, 2020;. Under homeostatic conditions, these epithelial niches produce daughter cells that contribute to the continuous turnover of the epithelia (Byrd et al, 2019;Tanaka et al, 2021;Yuan et al, 2019Yuan et al, , 2023Yuan, Chen, Gauer, et al, 2020;. In response to injury, for example, extraction of a tooth, gingivectomy and placement of an implant, these same epithelial niches dramatically increase production of mitotically active daughter cells, which then migrate widely to occupy and heal the damaged areas (Yuan et al, 2021;Yuan, Chen, Gauer, et al, 2020;.…”
Section: A Model To Explain the Rate Of Pie Maturationmentioning
confidence: 99%
“…And if so, from where does this second cell population originate? We know something about the mechanisms, both physical and/or biological, that contribute to establishment of a JE stem cell niche (Yuan et al, 2023); could these same factors be reactivated to create a stem cell niche around implants? These questions form the basis of ongoing investigations by our group into methods to accelerate and rejuvenate barrier functions to the PIE.…”
Section: A Model To Explain the Rate Of Pie Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal health is difficult to maintain as the periodontium must steadily defend against the microbial and other burdens inherent to the oral cavity [ 1 , 2 , 3 ]. There is also mechanical damage to the gingiva coming from exaturated mastication that the periodontium has to deal with [ 4 ], however, physiological masticatory loaging is required for periodontal homeostasis [ 5 ]. Thus, the gingiva and the junctional epithelium with the periodontal ligament underneath build a vital barrier toward the oral cavity equipped with a defense system driven by inflammation [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%